RACISM IN SING, UNBURIED, SING BY JESMYN WARD AND AN AMERICAN MARRIAGE BY TAYARI JONES - Cindy Zahra Devita,S.S., M.Hum. (Jurnal Sastra - Studi Ilmiah Sastra, 2022)
This thesis, entitled Racism in Sing, Unburied, Sing (2017) by Jesmyn Ward and An American Marriage (2018) by Tayari Jones aims at conveying racism in Sing, Unburied, Sing and An American Marriage. This research shows that racism is socially constructed and shows that the relationship between races will be a problem for black and white people, as well for the half African-American children. In addition, it will also be seen that racism in the United States will give a negative stigma and negative impact on black people.